1996
DOI: 10.1259/0007-1285-69-821-437
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of doses and techniques between specialist and non-specialist centres in the diagnostic X-ray imaging of children

Abstract: A dosimetric survey of 14 routine X-ray examinations in children was carried out between 1993 and 1995. Two children's hospitals and four general hospitals took part in the survey which involved the calculation and measurement of nearly 3000 doses. Entrance surface doses (ESD) were calculated from exposure factors for radiographic procedures, and dose-area products (DAP) were recorded for both radiographic and fluoroscopic procedures. Doses were in good agreement with earlier studies, but for some procedures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 9 publications
(18 reference statements)
2
17
0
4
Order By: Relevance
“…The ESAKs recorded in this study following changes in tube potential were comparable with other studies [10,12,13]. A survey of ESAKs in adult chest radiography in Malaysia found wide variation in doses [2].…”
Section: Discussionsupporting
confidence: 87%
“…The ESAKs recorded in this study following changes in tube potential were comparable with other studies [10,12,13]. A survey of ESAKs in adult chest radiography in Malaysia found wide variation in doses [2].…”
Section: Discussionsupporting
confidence: 87%
“…in the absence of 0.1 mm Cu) was determined from the measured half-value layer in aluminium. Since most authors had reported the entrance dose as a dose-in-air including backscatter [22, 23, 2531], we followed this convention. We estimated backscatter factors for the conversion of incident air kerma to entrance dose for each age group and radiation quality using data from the NRPB report R279 [36].…”
Section: Methodsmentioning
confidence: 99%
“…Radiation doses to children from common X rays show substantial variations between hospitals within the same time period and geographic territory (29)(30)(31)(32)(33)(34) Genes involved in DNA repair are critical for maintaining the integrity of genetic material transmitted from one cell to another and for protection against mutations leading to cancer. Mammalian cells rely on DNA repair systems to maintain their genomic integrity.…”
Section: Resultsmentioning
confidence: 99%